Globalization and Its Impact on the Consumption Pattern of Female University Students: An Applied Study on University of Hail Female Students - Al-Sayed, Afaf Ali; Al-Siddiq, Fathia Mohammed; Al-Aqili, Lamia Saud (Journal of Humanities & Social Sciences, 2025)
This study aims to specify the indicators that highlight consumption pattern and trends of female university students, considering the economic circumstances that are undergone by society and the extent to which it was affected by globalization of economy and world trade. The study also aims to determine the economic and social dimensions that influence consumption pattern of university students, and the nature of differences in consumption patterns among various age categories, in addition to dealing with verifying the existence of a correlation between consumption pattern and conversion from family values into individual values. The researcher adopted the analytical descriptive approach and employed the questionnaire as a tool for gathering the data of the study sample that consisted of University of Hail female students. The most prominent results that were concluded by the study were as follows: conversion from family values into individual values related to consumption pattern options, and conversion from traditional values into values of modernity. The benefits of the study can include recognizing the extent of study sample turnout towards goods and merchandize, which aids to setting strategies of promotion and marketing for domestic products.